Comparison of Mitochondrial Respiration in M. triceps brachii and M. vastus lateralis Between Elite Cross-Country Skiers and Physically Active Controls - Berg, Jonathan; Undebakke, Vidar; Rasch-Halvorsen, Øystein; Aakerøy, Lars; Sandbakk, Øyvind; Tjønna, Arnt Erik (Frontiers in Physiology, 2019)
Rationale: The main purposes of this study were to compare mitochondrial respiration in M. triceps brachii and M. vastus lateralis between elite cross-country (XC) skiers and physically active controls (CON), and to explore the associations between mitochondrial respiration in these muscles and peak oxygen uptake (V̇O2peak) in arm- and leg-dominant exercise modes. Method: Thirteen male elite XC skiers (age: 25 ± 4; peak oxygen uptake (V̇O2peak): 75.5 ± 4.2 mL.kg-1.min-1) and twelve CON (age: 26 ± 3; V̇O2peak: 57.2 ± 6.4 mL.kg-1.min-1) had microbiopsies taken from M. vastus lateralis and M. triceps brachii, which were analyzed for various measures of mitochondrial respiration using high-resolution respirometry. Thereafter, all participants tested V̇O2peak in both running (RUN) and upper body poling (UBP). Results: XC skiers had generally higher mitochondrial respiration in M. triceps brachii compared to CON (P<0.001), whereas no significant group-differences in mitochondrial respiration in M. vastus lateralis were revealed. XC skiers had higher mitochondrial respiration in M. triceps brachii compared to M.vastus lateralis (P=0.005-0.058), whereas in CON, most mitochondrial respiration measures were higher in M. vastus lateralis than in M. triceps brachii (P<0.01). When all athletes were pooled, there was a strong positive correlation between V̇O2peak in UBP and mitochondrial respiration in M. triceps brachii on several measures (P<0.01), whereas no correlation was found for RUN. Conclusion: The superior mitochondrial respiration found in M. triceps brachii compared to M. vastus lateralis among our elite XC skiers demonstrates the potential for the arm muscles to adapt to aerobic endurance training. The opposite pattern found in CON, clearly showed lower mitochondrial respiration in M. triceps brachii compared to XC skiers, whereas respiration in M. vastus lateralis did not differ between groups. The strong positive correlation between mitochondrial respiration in M. triceps brachii and V̇O2peak in UBP indicate that arm muscles’ respiratory function may be a limiting factor for V̇O2peak in arm-dominant exercise modes.